Untie, unfold… renew - Celiberti, Lilian Elmira (FCL-UNESP Laboratório Editorial, 2016)
This paper discusses how the construction of the feminist subject in Latin America opens up new theoretical approaches through which to analyze the experiences undergone by women under the dictatorships of the Southern Cone. If we can talk about gender violence in these dictatorships today it is because feminism has created a space where collective enunciation assumes the existence of a subject who is capable of politicizing her experience and thus of opening up a field of debate with other social actors about the meanings of these experiences. To develop this idea, I have constructed an argument centered on the three verbs used by the feminist movement in Latin America during the celebration of its thirtieth year: to untie, to unfold, and to re-entangle. My aim is to show that certain categories that are perceived as neutral by the hegemonic culture may not be when the social experience of women – read from a feminist perspective – enters the public debate. Thus, I hope to bring to the fore dissonant aspects and hidden meanings that have been concealed up until now.